Regioselective Photooxidation of Citronellol: A Way to Monomers for Functionalized Bio-Polyesters - Lanteri, Deianira; Quattrosoldi, Silvia; Soccio, Michelina; Basso, Andrea; Cavallo, Dario; Munari, Andrea; Riva, Renata; Lotti, Nadia; Moni, Lisa (Frontiers in Chemistry, 2020)
Dye-sensitized photooxygenation reaction of bio-based double bond-containing substrates is proposed as sustainable functionalization of terpenes and terpenoids to transform them into polyoxygenated compounds to be employed for the synthesis of new bio-based polyesters. As proof of concept, citronellol 1 has been regioselectively converted into diol 4 using singlet oxygen (1O2), a traceless reagent that can be generated from air, visible light and zeolite supported-photosensitizer (Thionine-NaY). With our synthetic approach, diol 4 has been obtained in two-steps, with good regioselectivity, using green reagents such as light and air, and finally a solvent-free oxidation step. From this compound, a citronellol-based copolyester of poly(butylene succinate) (PBS) has been synthesized and fully characterized. The results obtained evidence that the proposed copolymerization of PBS with the citronellol-based building blocks allows to obtain a more flexible and functionalizable material, by exploiting a largely available natural molecule modified through a green synthetic path.